The dark side of transparency in developing countries: The link between financial reporting practices and corruption - Liu, Tingting; Liu, Yu; Ullah, Barkat; Wei, Zuobao; Xu, Lixin Colin (Journal of Corporate Finance, 2021)
This paper examines the impact of financial reporting practices on corruption obstacles for about 150,000 firms across 143 mostly developing countries from 2006 to 2019. We document a strong positive relationship between the production of audited financial statements (AFS) and corruption obstacles (CO) faced by the firm. We argue that in a corrupt business environment, rent-seeking bureaucrats use the credible financial information to optimize their bribe demands. Our baseline results remain robust after addressing endogeneity concerns. We further show that country-level institutional quality has a moderating effect on the AFS-CO relation. The evidence from surveying entrepreneurs also provides qualitative support for our empirical findings. Our study sheds light on a previously under-explored adverse consequence of transparency - exposure to corrupt bureaucrats where institutions are weak.